CORRELATION BETWEEN STUDENT’S VOCABULARY MASTERY AND SPEAKING SKILL - Taslim, Taslim; Asrifan, Andi; Chen, Yan; NR, Nurdania (JOURNAL OF ADVANCED ENGLISH STUDIES, 2019)
The objective of the research was at measuring correlation between student’s mastery vocabulary and speaking skill of the eleventh grade at SMAN 6 Sidrap. Variables of the research were the student’s mastery vocabulary as independent variable (x) and speaking skill as dependent variable (y). In this study, the researcher used correlation design, where the researcher used this design to correlate two variables. The population of this research was all of the eleventh grade (XI2) students of IPA class at SMAN 6 Sidrap and the number of the subject was thirty-two students. In collecting the data, the researcher used some test was vocabulary test and interview. In this research, the researcher used cluster sampling technique to chosen classes. The researcher analyzed the data using Pearson Product Moment Correlation and Linear Regression with SPSS 21 program to test the hypothesis. The result of calculation using SPSS 21 program found that the rvalue 0.532 was also higher than rtable at 5% and 1% significant level or 0.349 < 0.532 > 0.449. It could be concluded that alternative hypothesis (H1) stating that there is a significant positive correlation between student’s mastery vocabulary and speaking skill of the eleventh grade at SMAN 6 Sidrap is accepted and null hypothesis (H0) stating there is no a significant positive correlation between student’s mastery vocabulary and speaking skill of eleventh grade at SMAN 6 Sidrap is rejected. The result of calculation of contribution between student’s mastery vocabulary (variable X) gave about 75.33% contribution to the speaking skill (variable Y) of the sample class and 25.66% was influenced by other aspects. Based on the research findings, in is shown that there is a very significant positive correlation between student’s mastery vocabulary and speaking skill of the eleventh grade at SMAN 6 Sidrap. It meant that the student who had lack of vocabulary